2014
DOI: 10.1103/physrevlett.112.130404
|View full text |Cite
|
Sign up to set email alerts
|

LocalPTSymmetry Violates the No-Signaling Principle

Abstract: Bender et al. [Phys. Rev. Lett. 80, 5243 (1998)] have developed PT-symmetric quantum theory as an extension of quantum theory to non-Hermitian Hamiltonians. We show that when this model has a local PT symmetry acting on composite systems, it violates the nonsignaling principle of relativity. Since the case of global PT symmetry is known to reduce to standard quantum mechanics A. Mostafazadeh [J. Math. Phys. 43, 205 (2001)], this shows that the PT-symmetric theory is either a trivial extension or likely false a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
182
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(193 citation statements)
references
References 38 publications
6
182
2
3
Order By: Relevance
“…because the observers live in the conventional quantum world [15,29,30]. The quantum average of an observable A can then be calculated as…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
See 1 more Smart Citation
“…because the observers live in the conventional quantum world [15,29,30]. The quantum average of an observable A can then be calculated as…”
Section: Fig 1: (Color Online)mentioning
confidence: 99%
“…For example, Bender et al [14] found that the evolution time between two quantum states under the PT -symmetry operation can be arbitrary small. Lee et al [15] found that the nosignalling principle can be violated when applying the local PT -symmetric operation on one of the entangled particles.…”
mentioning
confidence: 99%
“…Although the concept of PTsymmetric quantum mechanics, as a fundamental theory, is still under a heated debate [27], it has been explored in optics and electronics by means of interleaving balanced gain-and-loss regions. Several interesting physical features have been explored, such as power oscillations [28], unidirectional invisibility [29][30][31][32], the reconfigurable Talbot effect [33], and coherent perfect laser absorbers [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…This mathematical discovery has initiated numerous studies of open systems with balanced gain and loss even though the generality of this construction is under discussion [3]. Experimental setups have been offered to create PT -symmetric physical systems in optics [4][5][6][7][8], electronic circuits [9][10][11], as well as in mechanical systems [12].…”
Section: Introductionmentioning
confidence: 99%